QUEM GERA O TEMA GERADOR? - Arnholz, Erineti (2020)
This work raises through a concern about the methods in the dissemination of scientific knowledge in the school environment, based on understanding of the proposed subjects need to be approached in the context of the classroom to motivate the teachers to